Response to live high, train low among elite Olympic distance triathletes - Hiller, W. D. B.; Dierenfield, L. M.; Fortess, E. E.; Nielsen, G. R.; Pinkert, T. P.; Scudder, D. A.; Wong, D. L.; Thrower-Rodriguez, T. R.; Yamada, D. S.; Forde, K. J.; Jensen, S. (Medicine & Science in Sports & Exercise, 2001)
The purpose of this study was to evaluate the effect of "live high, train low" (LHTL) on a group of Olympic distance (1.5 K swim, 40 K bike, 10 K run) triathletes. Two groups, a total of 22 males, and 12 females aged 17-35 lived for 30 days and 38 days, respectively, at 2100 m and commuted daily to train at sea level. Athletes were from Hungary, Czech Republic, Australia, Yugoslavia, Mexico, New Zealand, and the United States. Prior to LHTL they underwent comprehensive lab testing including incremental VO2~x/treadmill, complete blood work, and body composition analysis with air-displacement plethsymography and full body dual x-ray absorptiometry (DXA). All tests were repeated weekly for a total of five test sets in the first group, and six in the second group. Athletes continued their own training plans, and acted as their own controls. RESULTS; VO2~~ /treadmill increased in both groups by 8% over the study duration. Changes in blood indices, and body composition will be discussed. Overall, 17 males, and 10 females responded to the regimen (defined by a >2% increase in VO2ma. treadmill), while 5 males, and 2 females did not. CONCLUSION: For some athletes, LHTL potentially offers performance gains as shown by significant changes in several physiological indices over short period of time.